Ratio Decidendi and the Constitutional Court Jurisprudence in Examining Constitutional Rights of Single Candidate in Regional Head Election - Anwar Usman (Lex Publica, 2017)
The first wave of simultaneous regional elections in 2015 emerged a new phenomenon: several regions that carried out regional elections had one pair of candidates. So there is a possibility that the celebration of the local democratic party at that time will have to be postponed, bearing in mind Law No. 8 of 2015 requires that regional elections can take place if there are at least two pairs of candidates contestations. The method used in this research will examine the main issues through a case approach, namely examining the ratio decidendi in the Constitutional Court decisions, which are the object of research, and the statutory approach. The data analysis method is a qualitative analysis and is presented in a descriptive form. The legal problems of a single regional head candidate in the simultaneous regional head elections in 2015 were motivated by negligence in the legislative process of Law No. 8 of 2015 regarding the emergence of the phenomenon of a single regional head candidate in several regions. The Pilkada Law requires that regional head elections have a minimum of two pairs of candidates in each region. However, on a das sein basis, three regions have only one pair of regional head candidates at the end of the registration extension period. Against this condition, a single-candidate solution emerged from the Indonesian General Elections Commission (Komisi Pemilihan Umum/KPU) with the issuance of General Election Commission Regulation No. 12 of 2015, which contains the postponement of the implementation of elections for regions with only one pair of candidates. Based on these conditions, Constitutional Court Decision No. 100/PUU-XIII/2015 provides a solution whereby regions with a single candidate can still carry out Pilkada so that the constitutional rights of the people in the area are not lost. For the constitution to live and be reflected in the administration of the state and the citizens’ daily lives, the Constitutional Court and other state components must approach and make constitutional thoughts. This task is the responsibility of all state institutions, government agencies, and citizens. Abstrak Pilkada serentak gelombang pertama tahun 2015 muncul fenomena baru, di mana beberapa daerah yang melaksanakan Pilkada hanya mempunyai satu pasangan calon. Sehingga ada kemungkinan perayaan pesta demokrasi lokal kala itu harus tertunda, mengingat Undang-Undang No.8 tahun 2015 mensyaratkan bahwa Pilkada dapat berjalan apabila minimal ada dua pasangan calon yang bertarung. Metode yang digunakan penelitian ini akan mengkaji pokok permasalahan melalui pendekatan kasus, yakni mengkaji ratio decidendi dalam putusan Mahkamah Konstitusi yang menjadi objek penelitian dan pendekatan perundangundangan (statute approach). Adapun metode analisis data yang digunakan adalah analisis kualitatif dan disajikan dalam bentuk deskriptif. Problematika hukum calon tunggal kepala daerah dalam pemilihan kepala daerah serentak di 2015 dilatarbelakangi oleh kealpaan proses legislasi Undang-Undang No. 8 Tahun 2015 terhadap munculnya fenomena calon tunggal kepala daerah di beberapa daerah. Undang-undang Pilkada menghendaki bahwa pemilihan kepala daerah memiliki minimal dua pasangan calon di masing-masing daerah. Akan tetapi, secara das sein terdapat tiga daerah yang pada akhir masa perpanjangan pendaftaran hanya memiliki satu pasangan calon kepala daerah. Terhadap kondisi demikian muncul solusi calon tunggal yang berasal dari Komisi Pemilihan Umum (KPU) dengan dikeluarkannya Peraturan Komisi Pemilihan Umum No. 12 Tahun 2015 yang berisi penundaan pelaksanaan pemilihan bagi daerah yang hanya memiliki satu pasangan calon. Atas kondisi tersebut, Putusan MK No. 100/PUU-XIII/2015 memberikan solusi daerah-daerah dengan calon tunggal tetap dapat melaksanakan Pilkada agar hak konstitusional masyarakat di daerah tersebut tidak menjadi hilang. Agar konstitusi dapat hidup dan tercermin dalam penyelenggaraan negara dan keseharian hidup warga negara, Mahkamah Konstitusi dan komponen negara lainnya harus mendekatkan dan menjadikan pemikiran-pemikiran konstitusional. Tugas inilah yang menjadi tanggungjawab seluruh lembaga negara, lembaga pemerintah, dan setiap warga negara. Kata Kunci: Hak Konstitusional, Ratio Decidendi, Yurisprudensi, Pemilihan Kepala Daerah, Mahkamah Konstitusi